2018
DOI: 10.12912/23920629/99550
|View full text |Cite
|
Sign up to set email alerts
|

Newest recognition of exploitation parameters based on Chochołów PIG-1 borehole in the aspect of temperature effect

Abstract: STRESZCZENIE W obszarze niecki podhalańskiej funkcjonuje kilkanaście otworów hydrogeologicznych ujmujących wodę termalną. Jednym z nich jest otwór Chochołów PIG-1 eksploatowany na potrzeby kompleksu rekreacyjnego Chochołowskie Termy. W listopadzie 2017 roku przeprowadzono w przedmiotowym otworze badania hydrogeologiczne w celu korekty podstawowych parametrów hydrogeologicznych związanych z eksploatacją ujęcia tj. wyznaczenia jego zasobów eksploatacyjnych i dopuszczalnego obniżenia zwierciadła wód termalnych. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…The analysis confirmed the studies conducted by many scientists which revealed that the chemical composition of geothermal water of the Podhale Trough is stable over time [33,37,[56][57][58][59][60]. The results of our study were compared to archival data and are in the range of natural changes in the chemical composition of investigated geothermal water (Figure S1).…”
Section: Resultssupporting
confidence: 88%
“…The analysis confirmed the studies conducted by many scientists which revealed that the chemical composition of geothermal water of the Podhale Trough is stable over time [33,37,[56][57][58][59][60]. The results of our study were compared to archival data and are in the range of natural changes in the chemical composition of investigated geothermal water (Figure S1).…”
Section: Resultssupporting
confidence: 88%
“…Most wells are self-flowing due to high artesian pressure (up to 27 bar). Wellhead temperature of produced water varies from 20 °C in the southern part of the system up to 90 °C in the central and western part (Kępińska 2006;Miecznik 2017;Bielec and Operacz 2018). Waters' mineralization ranges from below 1 to ca 3 g/dm 3 .…”
Section: A Brief Overview Of Geothermal Conditions In Polandmentioning
confidence: 99%